Bromadiolone susceptibility in wild and laboratory Mus musculus L.(house mice) in Buenos Aires, Argentina - Guidobono, Juan Santiago (2010)
BACKGROUND: Rodents are major pests in many agricultural systems, where they can cause significant economic losses and involve a sanitary risk. The application of anticoagulant rodenticides for rodent control has showed a decrease in effectiveness through time because of the development of resistant populations and the development of aversion behaviour. The goal of the present study was to test the susceptibility to bromadiolone and the existence of anticoagulant resistance in Mus musculus L. (house mouse) in Argentina. We conducted a feeding test with wild animals captured in poultry farms and a laboratory strain that were fed with bromadiolone bait. RESULTS: Three animals of the field experimental group survived the 21 days study period, while for laboratory animals mortalitywas 100%. Control field animals which were fed without anticoagulant showed 100% survival. CONCLUSION: We found evidence of the presence of anticoagulant resistant M. musculus in the study area. Feeding behaviour may have contributed to increasing the time of survival, and may be a mechanism that allows metabolic clearance of the bromadiolone. Under field conditions control with anticoagulants would be less effective because animals have alternative food.